Systematic Review and Pharmacological Considerations for Chloroquine and Its Analogs in the Treatment for COVID-19 - Peng, Hongwei; Chen, Zhangren; Wang, Yunyun; Ren, Simei; Xu, Tiantian; Lai, Xin; Wen, Jinhua; Zhao, Mengjun; Zeng, Chuanfei; Du, Lijuan; Zhang, Yanmei; Cao, Li; et al. (Frontiers in Pharmacology, 2020)
COVID-19 has been announced pandemic by WHO and over 17,000,000 people infected(Till 21st April 2020) . The disease is almost under control in China with the curative rate 86.8%. Chloroquine(CQ) is an old anti-malarial drug with good tolerability generally, which had proved to be effective in previous SARS-coronavirus which spread and disappearred between 2002-2003 and in vitro studies demonstrated its efficacy in COVID-19. Consequently, via rational PBPK modelling, further multicenter clinial trial has proved the efficacy and safety of CQ in China., multiple clinical trials were registered considering the application of other analogs of CQ against COVID-19. As CQ and its analogs have special pharmacokinetic characteristics, which would induce severe side effects in some circumstances. Here we summerized pharmalogical considerations for these drugs, so as to provide to the busy clinicians to avoid potential side effects when administered CQ or its analogs to COVID-19 patients, especially in the elderly, pediatrics and pregnancies.